Khai triển: A=(x-1+y)^2.
B=(x-y+2)^2.
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) (x - 1/2x²y)²
= x² - 2x . 1/2 x²y + (1/2x²y)²
= x² - x³y + 1/4 x⁴y²
b) (2xy² - 1)(1 + 2xy²)
= (2xy²)² - 1²
= 4x²y⁴ - 1
c) (x - y + 2)²
= (x - y)² + 2(x - y).2 + 2²
= x² - 2xy + y² + 4x - 4y + 4
= x² + y² - 2xy + 4x - 4y + 4
d) (x + 1/2)(1/2 - x)
= (1/2)² - x²
= 1/4 - x²
e) (x² - 1/3)²
= (x²)² - 2x².1/3 + (1/3)²
= x⁴ - 2/3 x² + 1/9
A=\(x^2+y^2+z^2+2xy+2yz+2xz\)
B=\(x^2+y^2+z^2-2xy+2yz-2xz\)
C=\(x^2+y^2+z^2-2xy-2yz+2xz\)
D=\(x^2+4y^2+1+2x-4y-4xy\)
TL:
\(A=x^2+y^2+z^2+2xy+2yz+2xz\)
\(B=x^2+y^2+z^2-2xy+2yz-2xz\)
\(C=x^2+y^2+z^2-2xy-2yz+2xz\)
\(D=x^2+1+4y^2+2x-4y+4xy\)
hc tốt
a) \(\left(\dfrac{x^2}{2}+y^2\right)^2\)
\(=\left(\dfrac{1}{2}x^2+y^2\right)^2\)
\(=\left(\dfrac{1}{2}x^2\right)^2+2\cdot\dfrac{1}{2}x^2\cdot y^2+\left(y^2\right)^2\)
\(=\dfrac{1}{4}x^4+x^2y^2+y^4\)
b) \(\left(\dfrac{4}{5}x^2-\dfrac{2}{3}y\right)^2\)
\(=\left(\dfrac{4}{5}x^2\right)^2-2\cdot\dfrac{4}{5}x^2\cdot\dfrac{2}{3}y+\left(\dfrac{2}{3}y\right)^2\)
\(=\dfrac{16}{25}x^4-\dfrac{16}{15}x^2y+\dfrac{4}{9}y^2\)
c) \(\left(2x+\dfrac{1}{2}\right)\left(2x-\dfrac{1}{2}\right)\)
\(=\left(2x\right)^2-\left(\dfrac{1}{2}\right)^2\)
\(=4x^2-\dfrac{1}{4}\)
a: (1/2x^2+y^2)^2
=(1/2x^2)^2+2*1/2x^2*y^2+y^4
=1/4x^4+x^2y^2+y^4
b: (4/5x^2-2/3y)^2
=(4/5x^2)^2-2*4/5x^2*2/3y+4/9y^2
=16/25x^4-16/15x^2y+4/9y^2
c: =(2x)^2-(1/2)^2
=4x^2-1/4
Câu 3:
a: \(49^2=2401\)
b: \(51^2=2601\)
c: \(99\cdot100=9900\)
Bài 3:
a) \(4x^2+4x+1=\left(2x+1\right)^2\)
b) \(9x^2-12x+4=\left(3x-2\right)^2\)
c) \(ab^2+\dfrac{1}{4}a^2b^4+1=\left(\dfrac{1}{2}ab^2+1\right)^2\)
Ta có : A = (x - 1 + y)2
= [(x - 1) + y]2
= (x - 1)2 + 2(x - 1)y + y2
= x2 - 2x + 1 + 2xy - 2y + y2
= x2 + y2 + 1 - 2x - 2y + 2xy
A = (x - 1 + y)2
= [(x - 1) + y]2
= (x - 1)2 + 2(x - 1)y + y2
= x2 - 2x + 1 + 2xy - 2y + y2
= x2 + y2 + 1 - 2x - 2y + 2xy